Digital Processing To Improve The Clarity Of Historical Map Images Using Artificial Intelligence Techniques - Duraym, Abdullah M.; Hafez, Mohammed S (Al-Adab Journal, 2022)
Data processing and preparation are among the most important steps that precede any analytical process, and due to the importance of this topic related to the study of historical maps and the obstacles that may arise when studying images of historical maps, it was necessary to present these difficulties and find solutions to complete the subsequent analyzes to reach more accurate results. In most cases, it is not possible to obtain the original copies of historical maps for study, especially in the Arab world, but they are available on many international sites, which allow the process of downloading them with a certain accuracy that may not be suitable for the work of some analyzes related to historical maps. This study highlights the importance of improving the clarity and quality of digital historical map images imported from trusted websites, to reach clarity and ideal quality for making analyzes related to historical maps, especially in the field of evaluating their engineering accuracy after being inserted into specialized software environments. The study sought to take advantage of the general Artificial Intelligence software to process the images of the studied historical maps in order to increase the clarity of the map images through the Gigapixel AI program for doubling the number of image pixels in addition to improving its quality using the Sharpen AI program. The study concluded the importance of using artificial intelligence software to increase the clarity of images and improve their quality, and that this technique is effective for dealing with many digital historical maps downloaded from the World Wide Web, The study also found that the ideal resolution for the clarity of historical map images for the purpose of analysis lies between 5000-8000 pixels per inch.